Travels, Translations and Limitations: Ambasciatrice Caroline Crane Marsh - Etta Madden (Transatlantica)
Caroline Crane Marsh (1816-1901), wife of George Perkins Marsh, a U.S. diplomat to Turkey and Italy, deserves recognition for the ways in which her self-understanding was transformed by her travels abroad and translating practice. Caroline saw herself not only as dutiful wife or “handmaiden” to George, but also as surrogate mother, social activist, teacher, translator and aspiring author. Two volumes she translated into English, The Hallig or, the Sheepfold in the Waters: a Tale of Humble Life on the Coast of Schleswig (1856), and The Wolfe of the Knoll, and other Poems (1859), considered alongside her poetry, letters and journals, provide windows to the values of translation as a venue of negotiation and cultural exchange. Caroline’s translating work emerged in a period of American exceptionalism that celebrated the Anglo as ideal subject (if not imperial colonizer) and often occluded cultural difference that had been part of the Americas since European arrival. Yet her literary labors reflect that Caroline realized her role as a mediator rather than militaristic conqueror, with translations that make difference overt and journal entries that demonstrate she recognized her limitations as a reformer and a conveyor of religious “truth.” This emphasis on Caroline as translator contributes to an understudied area in discussions of American women’s travel writings, building from diverse views of translation in the nineteenth century and today.